Blood Safety: On-Site Verification Of The Screening Of HIV, HBV And HCV By Enzyme Linked Immuno-Sorbent Assay (ELISA) Kits From Bio-Rad Laboratories At The “Centre National De Transfusion Sanguine” (CNTS) Of Lomé In Togo - Gnatoulma Katawa; Christèle Nguepou Tchopba; Marthe Oukoé Amessoudji; Pelagie Edlom Tchadié; Simplice Damintoti Karou; Yaovi Ameyapoh; Liza Koboyo Nadjir; Ablam Ameyissa; Lochina Feteke; Esso-Mondjonna Tougoma (European Scientific Journal, ESJ, 2021)
Background: Blood transfusion improves health and saves lives. Safe blood must be ensured for our populations. Quality assurance is a process that includes a set of coordinated activities in order to achieve the quality objective. Compliance with the quality management rules of medical biology laboratories requires verification of methods prior to their use. This study aimed to verify the on-site verification of the performance of the Enzyme Linked Immuno-Sorbent Assay (ELISA) method performed at the serology laboratory of the CNTS of Lomé. Methods: The performance of ELISA method performed at the serology laboratory of CNTS for the diagnosis of HIV, Hepatitis B and C with Bio-Rad Genscreen ULTRA-HIV Ag-Ac, Bio-Rad Monolisa-HBs Ag ULTRA and Bio-Rad Monolisa HCV Ag-Ac ULTRA V2 kits respectively was evaluated on repeatability, reproducibility, sensitivity and specificity according to COFRAC's SH GTA 04 reference. Results: The evaluation of the repeatability and reproducibility of each kit used in the laboratory resulted in compliant Coefficients of Variation (CV) with manufacturers’ ones. Sensitivities obtained with Bio-Rad Monolisa HCV Ag-Ac ULTRA V2, Bio-Rad Monolisa HBs Ag ULTRA and Bio-Rad Genscreen ULTRA HIV Ag-Ac kits were 94.59%, 98.08% and 100% respectively. For specificity tests, we found 86.49% with BIO-Rad Genscreen ULTRA-HIV Ag-Ac kit, 94.34% with Bio-Rad Monolisa HCV Ag-Ac ULTRA V2 kit and 97.37% with Bio-Rad Monolisa-HBs Ag ULTRA. Conclusion: In general, results were compliant except HIV diagnosis specificity. This study appears as a contribution to the establishment of a verification file for ELISA method used at the serology laboratory of CNTS of Lomé.